Cell Populations Expressing Stemness-Associated Markers in Lung Adenocarcinoma - Claudia Paterson; Ethan J. Kilmister; Helen D. Brasch; Nicholas Bockett; Josie Patel; Erin Paterson; Gordon Purdie; Sean Galvin; Paul F. Davis; Tinte Itinteang; Swee T. Tan (Life, 2021)
The stemness-associated markers OCT4, NANOG, SOX2, KLF4 and c-MYC are expressed in numerous cancer types suggesting the presence of cancer stem cells (CSCs). Immunohistochemical (IHC) staining performed on 12 lung adenocarcinoma (LA) tissue samples showed protein expression of OCT4, NANOG, SOX2, KLF4 and c-MYC, and the CSC marker CD44. In situ hybridization (ISH) performed on six of the LA tissue samples showed mRNA expression of OCT4, NANOG, SOX2, KLF4 and c-MYC. Immunofluorescence staining performed on three of the tissue samples showed co-expression of OCT4 and c-MYC with NANOG, SOX2 and KLF4 by tumor gland cells, and expression of OCT4 and c-MYC exclusively by cells within the stroma. RT-qPCR performed on five LA-derived primary cell lines showed mRNA expression of all the markers except SOX2. Western blotting performed on four LA-derived primary cell lines demonstrated protein expression of all the markers except SOX2 and NANOG. Initial tumorsphere assays performed on four LA-derived primary cell lines demonstrated 0–80% of tumorspheres surpassing the 50 µm threshold. The expression of the stemness-associated markers OCT4, SOX2, NANOG, KFL4 and c-MYC by LA at the mRNA and protein level, and the unique expression patterns suggest a putative presence of CSC subpopulations within LA, which may be a novel therapeutic target for this cancer. Further functional studies are required to investigate the possession of stemness traits.